2012
DOI: 10.1242/jcs.113902
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin G is involved in meiotic recombination repair inDrosophila melanogaster

Abstract: SummaryCyclin G (CycG) belongs to the atypical cyclins, which have diverse cellular functions. The two mammalian CycG genes, CycG1 and CycG2, regulate the cell cycle in response to cell stress. Detailed analyses of the role of the single Drosophila cycG gene have been hampered by the lack of a mutant. We generated a null mutant in the Drosophila cycG gene that is female sterile and produces ventralised eggs. This phenotype is typical of the downregulation of epidermal growth factor receptor (EGFR) signalling d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(44 citation statements)
references
References 50 publications
0
43
0
Order By: Relevance
“…This strategy led to the generation of the cycG HR7 mutant allele, which is a protein null as determined by Western blots (Nagel et al in press). We noted that flies devoid of CycG are homozygous viable, however that the females are sterile (Nagel et al in press). This result was unexpected since RNAi‐ mediated depletion of cycG during early Drosophila development caused lethality implying that cycG was an essential gene (Salvaing et al 2008a).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…This strategy led to the generation of the cycG HR7 mutant allele, which is a protein null as determined by Western blots (Nagel et al in press). We noted that flies devoid of CycG are homozygous viable, however that the females are sterile (Nagel et al in press). This result was unexpected since RNAi‐ mediated depletion of cycG during early Drosophila development caused lethality implying that cycG was an essential gene (Salvaing et al 2008a).…”
Section: Resultsmentioning
confidence: 95%
“…Flies were obtained from the Bloomington and Umeå stock collections, respectively. Generation of the cycG HR7 mutant is described in Nagel et al (in press). Cytology of the following aberrations was studied on orcein stained salivary gland chromosomes of third instar larvae: In(3R)251 [88A5‐9; 100C5‐D1]; Df(3R)KpnA [100D1; 100E1‐E3]; Df(3R)E40 [100C5; 100F1‐F5].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, our analysis allowed us to define, for the first time, the family of atypical cyclins. Although atypical cyclins have been mentioned by several groups [66,81,103,108,109], they were never object of a comprehensive analysis to establish whether they could actually be included in the cyclin family or what defined them as atypical. We believe that the name atypical is the one that more accurately reflects the particularities of these cyclins and has already been used by several groups [66,81,103,108,109].…”
Section: Discussionmentioning
confidence: 99%
“…However, two genes were already reported as having a statistical association with recombination rate: CPLX1 and GAK (Augustine Kong et al 2014) . CPLX1 has no known function that can be linked to recombination (Augustine Kong et al 2014) but GAK has been shown to form a complex with the cyclin-G, which could impact recombination (Nagel et al 2012) . However, RNF212 can be deem a more likely candidate due to its function and given that this gene was associated with recombination rate variation in human (Chowdhury et al 2009) , (A.…”
Section: Lacaune Sheepmentioning
confidence: 99%